Upper Gastrointestinal Bleeding Revealing Renogastric Fistula: A Case Report and Literature Review. (20th March 2020) - Mellagui, Yassine; Haouli, Inass; Ouachaou, Jamal; Aabdi, Mohammed; Bkiyar, Houssam; Housni, Brahim
Abstract : A renogastric fistula is a rare complication defined by abnormal communication between the kidney and the stomach. We report the case of a patient admitted to the intensive care unit for hemorrhagic shock following upper gastrointestinal bleeding whose radiological investigations revealed a fistulated renal hematoma in the stomach.